Statistical global investigation of pre-earthquake anomalous geomagnetic diurnal variation using superposed epoch analysis - Yusof, Khairul Adib; Abdullah, Mardina; Abdul Hamid, Nurul Shazana; Ahadi, Suaidi; Ghamry, Essam (Institute of Electrical and Electronics Engineers, 2022)
Recent studies reported that the diurnal variation of the geomagnetic field exhibited anomalous characteristics several months before earthquakes (EQs). However, the statistical significance of such anomalies detected using the diurnal variation range ratio (DVRR) method still requires verification as only a limited number of EQs occurring in certain seismoactive zones were included. In this study, the DVRR method was employed in conjunction with the superposed epoch analysis (SEA) to perform a large-scale study. A total of 157 EQs that occurred between 2000 and 2019 were investigated using vast geomagnetic field data collected from 92 ground-based magnetometer stations spread across multiple global regions. The case study conducted on the May 13, 2011, M6.1 Honshu (Japan) EQ showed that the diurnal variation of the vertical geomagnetic component disappeared around a week before the EQ. The case study also demonstrated the effectiveness of the DVRR method in minimizing solar disturbance influences, further proving that the observed anomalies were not caused by the Sun. The subsequent SEA revealed statistically significant increases in anomaly counts before the occurrence of EQs for all three geomagnetic components. The number of anomalies gradually increased approaching the day of EQs with temporal lags between the components. Furthermore, a control group analysis confirmed the findings by demonstrating that the increases were not coincidental and several explanations have been suggested, focusing primarily on the emergence and generation mechanisms of the anomalies. Results from this study showed that the anomalies were significant and were potentially precursors to the succeeding EQs.